Antifungal and antioxidant activities and chemical constituents from Pluchea sagittalis (Research, Society and Development, 2022)
Pluchea sagittalis (Asteraceae) is widely distributed in South America and used as a medicinal plant to treat various diseases. The objectives of the work were to evaluate the antioxidant and antifungal activities of the ethanol extract and fractions from the aerial parts of P. sagittalis, as well as to identify the chemical constituents of the most active sample by liquid chromatography coupled to mass spectrometry with electrospray ionization (LC-MS-ESI). The ethanolic extract obtained by maceration of aerial parts showed relevant activity in DPPH free radical scavenging (IC50 = 33.9 µg mL-1) and presented an anti-Candida effect with MIC values of 93.75 µg mL-1 for C. albicans and 187 µg mL-1 for C. glabrata and C. tropicalis. However, the results found for the chloroform fraction prepared from the extract were more significant. This fraction showed the highest antioxidant activity with an IC50 of 12.5 µg mL-1 and inhibited the growth of Candida spp. with MIC values ranging from 46.87 to 93.75 µg mL-1. The qualitative phytochemical screening of this fraction indicated the presence of phenolic compounds and flavonoids. Twenty-three metabolites were identified by LC-MS in the chloroform fraction including caffeoylquinic acids derivatives, flavones and fatty acids, which have recognized antioxidant and antimicrobial effects. The results of the activities, as well as the chemical constituents present in the chloroform fraction, reveal the potential of this fraction as a source of antioxidant and antifungal agents.